2010
DOI: 10.1063/1.3515240
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Understanding of the Concepts of Vector Components and Vector Products

Abstract: In this article we investigate students' understanding of: 1) vector components and, 2) vector products. We administered a test to 409 students completing introductory physics courses at a private Mexican university. In the first part, based on the work of Van Deventer [1], we analyze the understanding of components of a vector. We used multiple-choice questions asking for students' reasoning to elaborate on the misconceptions and difficulties of graphical representation of the x-and y-components of a vector. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 1 publication
(2 reference statements)
1
21
0
2
Order By: Relevance
“…The results of some of our other studies based on open-ended problems have been reported in previous articles [23][24][25][26][27].…”
Section: A Development Of the Most Frequent Errors Taxonomymentioning
confidence: 58%
See 2 more Smart Citations
“…The results of some of our other studies based on open-ended problems have been reported in previous articles [23][24][25][26][27].…”
Section: A Development Of the Most Frequent Errors Taxonomymentioning
confidence: 58%
“…Previous studies of students' understanding of vector concepts can be clustered into three groups: (1) those that analyze their understanding of vector concepts in problems without a physical context [14][15][16][17][18][19][20][21][22][23][24][25][26][27], (2) studies that investigate their understanding in problems with a physical context [16][17][18][19]24,[27][28][29][30][31][32], and (3) studies that compare students' performance on both types of problems, with and without a physical context [17][18][19]24,27,31]. Note that some of these studies pertain to more than one group.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we studied these difficulties in an openended problem that asked students to interpret the dot product of two vectors (Zavala & Barniol, 2010), and then, based on the results, we constructed a multiplechoice option problem and analyzed students' difficulties with it (Zavala & Barniol, 2013). In this latter study, it was found that very few of the students completing the last of three introductory university physics courses had chosen the correct option.…”
Section: Previous Research On Students' Difficulties When Interpretinmentioning
confidence: 99%
“…To this end, a number of studies at the introductory level have investigated students' ability to add and subtract vectors (e.g. [3][4][5]), and students' understanding and execution of vector decomposition and vector products [6,7].…”
Section: Introductionmentioning
confidence: 99%